2013
DOI: 10.1080/01446193.2013.848995
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of construction productivity differences between Canada and the United States

Abstract: Comparisons of industry sectors in advanced economies since the 1960s show that the construction sector has lagged in productivity growth rates, especially in the United States. Although the US and Canadian economies are highly integrated, Canada's experience differs in key ways. Analysis of these differences offers insight into fundamental construction productivity drivers. Three levels of analyses of construction productivity in the US are provided in this study. The first analysis compared international lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Additionally, productivity is measurable at several levels (Kenley, 2014); from macroeconomic measures at the industry level which combine projects (Nasir et al, 2014) to microeconomic measures at the project level which combines activities and at the activity or task level (Meikle and Best, 2015).…”
Section: Productivitymentioning
confidence: 99%
“…Additionally, productivity is measurable at several levels (Kenley, 2014); from macroeconomic measures at the industry level which combine projects (Nasir et al, 2014) to microeconomic measures at the project level which combines activities and at the activity or task level (Meikle and Best, 2015).…”
Section: Productivitymentioning
confidence: 99%
“…The industry has also been challenged for poor performance on productivity. For example, Nasir et al (2014) compared the labour productivity of 20 countries and found that the US showed the worst performance with an annual compound rate of -0.84%. The low productivity issue has also been found in other developed countries, such as UK (Abdel-Wahab et al, 2008), Singapore (Lim and Alum, 1995) and Hong Kong (Lo et al, 2006).…”
mentioning
confidence: 99%
“…There is no single definition that can entirely describe productivity in a complex sector like the construction industry (Rane et al, 2017). Nasir et al (2014) opine that the reason for this is because different inputs and outputs are involved in different projects and organizations. For equipment-intensive construction operations, productivity is defined as output / input (i.e.…”
Section: Cost Indicatormentioning
confidence: 99%